Long term effectiveness of antimalarial drugs in rheumatic diseases. Issue 10 (1st October 1998) - Aviña-Zubieta, J Antonio; Galindo-Rodriguez, Griselda; Newman, Stephen; Suarez-Almazor, Maria E; Russell, Anthony S
Abstract : OBJECTIVE: The purpose of this study was to compare the long term effectiveness between chloroquine (CQ) and hydroxychloroquine (HCQ). METHODS: Medical charts of all patients seen by eight rheumatologists practising in two tertiary care centres and starting antimalarial treatment between January 1985 and December 1993 were reviewed. Patient characteristics, disease, and treatment information were collected. The main outcome measures were the cause of and the time to the discontinuation of antimalarial drugs resulting from all causes, principally toxicity or inefficacy, or both. Bivariate analysis including t tests and χ 2 tests were used to assess differences between means and proportions respectively. Survival curves were evaluated using the Kaplan-Meier method. Multivariate analysis (Cox regression) was used to adjust for potential confounders. RESULTS: After all medical records were reviewed, 1042 eligible cases were identified. From these, 940 (90%) had usable information and they represent the cohort. Five hundred and fifty eight had rheumatoid arthritis, 178 had systemic lupus erythematosus, 127 had palindromic arthritis, and 77 had other diagnoses. Fifty seven per cent of the patients received CQ and 43% HCQ. The proportion of patients with side effects taking HCQ and CQ was 15% and 28% respectively (p=0.001). Using Cox regression model to adjust for age at the onset of antimalarial treatment, physician differences, sex, disease type, disease duration before treatment, and rank selection, there were no differences in the hazard ratio (HR) for overall discontinuations between CQ and HCQ. While the HR for discontinuations because of toxicity was lower for HCQ (HR= 0.6, 95% CI 0.4, 0.9), the HR for discontinuations because of inefficacy was significantly higher for HCQ (HR= 1.4, 95% CI 1.1, 1.9). CONCLUSIONS: After adjusting for time and several confounders HCQ was less toxic but less effective than CQ. Only one case of probable/possible retinopathy was found. Therefore, we propose a careful baseline ophthalmological evaluation by an expert and then one or every two years if proper doses are used.